2008
DOI: 10.1159/000123611
|View full text |Cite
|
Sign up to set email alerts
|

Liver Position Is a Prenatal Predictive Factor of Prosthetic Repair in Congenital Diaphragmatic Hernia

Abstract: Objective: To determine whether any common maternal-fetal variable has prenatal predictive value of prosthetic repair in congenital diaphragmatic hernia. Methods: This was a 5-year single-center retrospective review of fetal congenital diaphragmatic hernia referrals. Multiple prenatal variables were correlated with the need for a prosthetic repair. Statistical analyses were by Fisher’s exact and Mann-Whitney U-tests, as appropriate (p < 0.05). Results: Fetal liver position was a predictor of prosthetic repair.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Liver herniation has long been considered an indicator of poor prognosis in fetuses with CDH. However, even though there is wide variation in the amount of liver herniated into the thorax, in most prior studies liver position has been considered to be solely a dichotomous variable (absent or present) which presents an analytical limitation.…”
Section: Discussionmentioning
confidence: 99%
“…Liver herniation has long been considered an indicator of poor prognosis in fetuses with CDH. However, even though there is wide variation in the amount of liver herniated into the thorax, in most prior studies liver position has been considered to be solely a dichotomous variable (absent or present) which presents an analytical limitation.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have examined ways to predict high-risk patients and mortality [13,14], but there have been very few convincing demonstrations that the high mortality associated with the highest risk patients can be ameliorated. Our inclusion criteria of looking at percentage of PLV less than 15% accurately predicated high risk.…”
Section: Discussionmentioning
confidence: 99%
“…Use of patch also increases the number of ventilator days and hospital stay and increases the risk of gastroesophageal reflux [56,57]. In the prenatal period, retrospective studies have shown that the need for a patch can be predicted by herniation of the liver as well as the O/E LHR [21,57,58]. In the CDH antenatal registry, prenatal liver herniation occurred in 42% of infants requiring patch repair compared with 17% of those primarily repaired [21].…”
Section: Cell-based Therapy For Cdh and Tissue Engineeringmentioning
confidence: 99%